UGT1A1 polymorphisms associated with prolactin response in risperidone-treated children and adolescents with autism spectrum disorder. Issue 6 (December 2018) - Hongkaew, Yaowaluck; Medhasi, Sadeep; Pasomsub, Ekawat; Ngamsamut, Nattawat; Puangpetch, Apichaya; Vanwong, Natchaya; Chamnanphon, Monpat; Limsila, Penkhae; Suthisisang, Chuthamanee; Wilffert, Bob; Sukasem, Chonlaphat
Abstract The aim of this study was to investigate the association of drug-metabolizing enzyme and transporter (DMET) polymorphisms with the risperidone-induced prolactin response using an overlapping gene model between serum prolactin level and hyperprolactinemia in autism spectrum disorder (ASD) patients. Eighty-four ASD patients who were receiving risperidone for at least 1 month were recruited and then assigned to either the normal prolactin group or the hyperprolactinemia group based on their serum prolactin level. The genotype profile of 1936 (1931 single nucleotide polymorphisms (SNPs) and 5 copy number variation (CNVs) drug metabolism markers was obtained using the Affymetrix DMET Plus GeneChip microarray platform. Genotypes of SNPs used to test the accuracy of DMET genotype profiling were determined using TaqMan SNP Genotyping Assay kits. Eighty-four patients were selected for the allelic association study after microarray analyses (51 in the normal prolactin group, and 33 in the hyperprolactinemia group). An overlapping allelic association analysis of both analyses discovered five DMET SNPs with a suggestive association (P  < 0.05) with risperidone-induced prolactin response. ThreeUGT1A1 SNPs (UGT1A1 *80c.-364C > T, UGT1A1 *93 c.-3156G > A, andUGT1A1 c.-2950A > G, showed a suggestive association with the risperidone-induced prolactin response and found to be in complete linkage disequilibrium (D′ value of 1). In this DMET microarray platform, we found threeUGT1A1 variants with suggestive evidences of association with the risperidone-induced prolactin response both measured by hyperprolactinemia and by prolactin level. However, due to the lack of validation studies confirmation and further exploration are needed in future pharmacogenomic studies.